PENGEMBANGAN BAHAN AJAR INTERAKTIF BERBASIS CANVA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI MIN 2 KOTA PALANGKA RAYA - Muhammad Syabrina; Istiyati Mahmudah; Lira Meini Meini; Salia Rahmawati (Al-mujahidah, 2026)
Pancasila education is an important subject that aims to instill Pancasila values ​​in students' daily lives. However, monotonous and uninteresting learning often causes students to lose motivation to learn. In this era of technological progress, creative, innovative and interactive learning media are needed to increase the effectiveness and attractiveness of learning. In this era of technological progress, creative, innovative and interactive learning media are needed to increase the effectiveness and attractiveness of learning. This research aims to create interactive, visual and easily accessible teaching materials using the Canva platform, as well as testing its feasibility and effectiveness in the learning process. The method used is development research using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, involving validation from material experts, design experts, teachers, as well as field trials on class IV B MIN 2 students in Palangka Raya City. The validation results show a very high level of feasibility, namely 92% material expert, 93% design expert, 75% teacher assessment, and 90% student response. Data analysis through the T Test and N-Gain confirmed a significant increase in learning outcomes with an average N-Gain value of 0.44 (medium category). Thus, it can be concluded that the Canva-based interactive teaching materials developed are proven to be feasible, effective, and capable of encouraging more interesting and meaningful learning for students.